Manajemen Pemasaran Pendidikan Dalam Meningkatkan Minat Peserta Didik Di Mts Pangeran Diponegoro - Mu’nisa, Qorinatul; Musolin, Muhlil; Lailiyah, Rosyidah Nur (JURNAL MANAJEMEN PENDIDIKAN, 2026)
EDUCATIONAL MARKETING MANAGEMENT IN INCREASING STUDENT INTEREST IN MTs PANGERAN DIPONEGORO The increasingly competitive world of education demands every educational institution to have effective educational marketing management. MTs Pangeran Diponegoro is one of the educational institutions that actively implements marketing management to increase student interest. This study aims to describe educational marketing management and its impact on increasing student interest at MTs Pangeran Diponegoro. This study uses a qualitative approach with a case study research type. Data collection techniques include in-depth interviews, observation, and documentation of parties such as the principal of the madrasah, the Deputy Head of Curriculum, the PPDB team, and students. Data analysis is carried out through the data reduction stage to compile relevant information, and emphasizes the core of educational marketing management, presentation of data presented in narrative form, drawing conclusions and verification. Triangulation techniques to ensure the validity of the data. The results of the study show that educational marketing management is carried out through: 1) educational marketing planning is carried out by determining the target market, developing educational marketing strategies to be carried out and designing superior programs from the madrasah; 2) organizing is carried out by forming a promotion team; 3) Promotion is carried out through various media, such as brochures, social media, open house activities, and outreach to elementary schools. 4) Marketing strategy evaluations are conducted periodically to ensure the program's relevance to community needs.